2019
DOI: 10.1038/s41597-019-0083-9
|View full text |Cite|
|
Sign up to set email alerts
|

33 years of globally calibrated wave height and wind speed data based on altimeter observations

Abstract: This dataset consists of 33 years (1985 to 2018), of global significant wave height and wind speed obtained from 13 altimeters, namely: GEOSAT , ERS-1 , TOPEX , ERS-2 , GFO , JASON-1 , ENVISAT , JASON-2 , CRYOSAT-2 , HY-2A , SARAL , JASON-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
208
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(217 citation statements)
references
References 37 publications
9
208
0
Order By: Relevance
“…2 Taylor diagram for annual mean of Hs (a) and H s 99 (b) of all global ocean region relative to the Satellite data over the period 1991-2017. The metrics shown are the spatial correlation (SC), normalized standard deviation (NSD) (given by σ sim /σ obs derived from a specific simulation and the satellite dataset 40 ) and the centred-root-mean-square (CRMSD) difference. The SC is shown by the azimuthal angle, the normalized standard deviation is shown by the radial distance from the origin (i.e., satellite data) and the CRMSD is shown by the distance from the origin (the yellow lines).…”
Section: Technical Validationmentioning
confidence: 99%
“…2 Taylor diagram for annual mean of Hs (a) and H s 99 (b) of all global ocean region relative to the Satellite data over the period 1991-2017. The metrics shown are the spatial correlation (SC), normalized standard deviation (NSD) (given by σ sim /σ obs derived from a specific simulation and the satellite dataset 40 ) and the centred-root-mean-square (CRMSD) difference. The SC is shown by the azimuthal angle, the normalized standard deviation is shown by the radial distance from the origin (i.e., satellite data) and the CRMSD is shown by the distance from the origin (the yellow lines).…”
Section: Technical Validationmentioning
confidence: 99%
“…It was assumed that the impact of oceanic and atmospheric parameters induces a "systematic error" which is similar for all altimeters using the same frequency band, and thus the data from Ka-band SARAL are not used here. All the altimeter U10 data used in this study were retrieved from Ku-band RCS as reported in [3], and the information of SWH and RCS of other frequencies (C-band and S-band) were not taken into consideration. The data with bad quality flags or U10 > 25 m/s or SWH > 10 m/s were discarded.…”
Section: Multiplatform Altimeter Datasetmentioning
confidence: 99%
“…Among these remote sensors, scatterometers have the widest swath and the best overall accuracy (with a typical error of ~1 m/s) [2], making them an irreplaceable data source of U10. Meanwhile, radar altimeters, with a typical error of wind speed of 1.5 m/s (e.g., [3,4]), have a better accuracy in high wind speeds [1] and can provide global coverage of U10 and significant wave height (SWH) data simultaneously, making them also a unique tool for studies in wind-waves (e.g., [5][6][7]). Since 1985, more than ten satellite altimeters have been launched, which provide sufficiently long data records for studies of wind and wave climate [5].…”
Section: Introductionmentioning
confidence: 99%
“…For wave data there are also three options (altimeters, synthetic aperture radar and CFOSat). A number of studies have already looked at global climatology of wind speed and wave height, including the Southern Ocean (Zieger et al, 2009;Vinoth and Young, 2011;Young et al, 2011Young et al, , 2017Takbash et al, 2018;Young and Donelan, 2018;Ribal and Young, 2019;Young and Ribal, 2019). These studies, however, are limited to wind speed and significant wave height and suffer from very limited possibilities for Southern Ocean Calibrations.…”
Section: Measurements In the Southern Oceanmentioning
confidence: 99%